Optimization design of hydraulic parameters for supercritical CO2 fracturing in unconventional gas reservoir. (1st January 2019) - Wang, Jintang; Wang, Zhiyuan; Sun, Baojiang; Gao, Yonghai; Wang, Xin; Fu, Weiqi
Graphical abstract: Highlights: The hydraulic parameters calculation model for supercritical CO2 fracturing in unconventional gas reservoir is proposed. According to the proppant embankment profile, the optimization proppant pumping process is recommended to satisfy the fracture propping requirements. Abstract: Unconventional gas reservoirs are characterized by ultra-low permeability. Such ultra-low permeability can significantly affect the geometry of the fractures being created in the reservoir, as well as bring about challenges with regard to how to effectively mitigate formation damage issues during fracturing. Supercritical CO2 (SC-CO2 ) fracturing, as an innovative and promising stimulation method, incurs no formation damage, and is capable of effectively improving the reservoir permeability, preventing near-wellbore formation blockage. Taking the effects of adsorption between CO2 -shale-CH4 into consideration, a two-phase filtration rate calculation model of SC-CO2 fracturing in unconventional natural gas reservoirs is proposed. Based on physical property equations of a SC-CO2 fluid, and considering the internal fluid energy, the change in flow work, and the filtration and adsorption characteristics of SC-CO2 -shale, temperature and pressure field models were built inside the wellbore and fracture of SC-CO2 fracturing, as was a two-phase flow model of SC-CO2 fracturing fluid carrying proppant in a fracture under an unsteady state. The calculation results show that the temperature and pressure of the fracturing fluid in the wellbore increase with the depth of the well. The temperature of the SC-CO2 fluid in the fracture increases with the increase in fracture length, and eventually reaches close to the original formation temperature, whereas the pressure of fluid CO2 in the fracture decreases with an increase in the fracture length. The hydraulic parameters of SC-CO2 fracturing are optimized, such as the CO2 injection temperature, pumping rate, proppant density, and diameter. According to the proppant embankment profile, the method of increasing the proppant concentration in small steps and the optimization of the proppant pumping process satisfy the fracture propping requirements.